Análise do necropercolado em diferentes meios hidrogeológicos ocupados por cemitérios - Fernandes, Gabriel D'Avila (2022)
Even after death, human beings continue to generate contaminants in the form of necroleachate, which may contain heavy metals and a series of other contaminants, altering the natural characteristics of water and soil. The present work aims to identify the behavior of necroleachate in cemeteries located in different hydrogeological environments and with different forms of burial in the State of Rio Grande do Sul. In this way, this work proposes a methodology for identifying the most appropriate areas for the installation of cemeteries, aiming to mitigate the negative impacts caused to the environment and public health, raising the hypothesis that takes into account that some natural characteristics are more determinant than characteristics constructive actions regarding mitigation of environmental impacts. If the natural characteristics are unfavorable, it is essential to adopt rigorous technical criteria that guarantee environmental quality. The physical characteristics of the soil were determined with granulometric analysis, the use of Guelph permeameter, and constant load in determining the permeability coefficient and saturated hydraulic conductivity respectively. To determine the water quality, Organic Matter, Dissolved Oxygen, Biochemical Oxygen Demand, Turbidity, and Alkalinity were quantified. In the chemical characterization of the soil, samples were collected using a Dutch manual auger at depths of 0, 0.5, and 1.5 m and determined by Atomic Absorption Spectrometry. A geophysical survey was carried out in order to identify the composition of the materials present in the subsoil, the depth of the water level, anomalies found, and the dimensions of the possible contamination zone. The electroresistivity method was used with the electric path technique, and the Dipole-Dipole arrangement, with intervals of 5 meters between the electrodes, the Cemetery Quality Index was also proposed as an instrument capable of identifying and characterizing the conditions in which the cemeteries meet and possible future scenarios, based on the peculiar characteristics of each cemetery and the local, natural characteristics of the environment. The case analysis was carried out in the cemeteries of Catacumba in Caçapava do Sul-RS, in the Municipal Cemetery Jardim da Saudade in Frederico Westphalen-RS, in the Cemetery Jardim da Saudade in Santa Maria-RS and in the Municipal Cemetery São Francisco in Tramandaí-RS. In the water quality analysis, for the turbidity parameter, the three municipalities where it was possible to collect samples showed values higher than the Maximum Permissible Values, the same occurred for the Biochemical Oxygen Demand. Using geophysics with the electroresistivity method and the electric path technique, possible contaminated areas were identified in the cemeteries of Caçapava do Sul-RS, Santa Maria-RS and Tramandaí-RS. After applying the Cemetery Quality Index, the cemeteries of Caçapava do Sul-RS and Frederico Westphalen-RS presented an Average condition, and Santa Maria-RS and Tramandaí-RS presented a very bad condition. It was possible to identify that sandy soils have a greater capacity for necroleach percolation, exposing groundwater to contaminants, justifying the construction of graves above ground level to mitigate these impacts. With the application of direct analysis techniques allied to the geophysical method, they proved to be an important tool for the sustainable management of areas occupied by cemeteries.